Teaching of infection control in undergraduate courses in health sciences: opinion of experts - Aline Massaroli; Jussara Gue Martini; José Luis Medina Moya; Julia Valéria de Oliveira Vargas Bitencourt; Kenya Schmidt Reibnitz; Mariely Carmelina Bernardi
ABSTRACT Objective: To know the perception of expert professionals in infection control and prevention on the teaching of skills for the prevention and control of infections related to health care in undergraduate courses in Health Sciences. Method: We used the Delphi technique, developed in four sequential rounds. Thirty-one nurses and eight physicians participated in the study. Qualitative data were analyzed through content analysis; the quantitative ones, from the descriptive statistics. Results: The importance of the courses has had teachers with expertise in infection control and prevention added to arguments about the development of the subject in the curricula by means of a specific subject or as a transversal theme. Conclusions: In order to cover the complexity of the elements that are interconnected for professional training, teaching must be based on pedagogical strategies that provoke reflection in students, encouraging them to develop critical thinking about their experiences.